Efektivitas Analgesik Ekstrak Etanol Daun Pegagan (Centella asiatica) Terhadap Mencit Putih (Mus musculus) - Siti Rahmadani; Lukman Hardia; Angga Bayu Budiyanto (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, representing a major health problem that requires effective management. Although synthetic analgesics are widely used, their long-term administration is often associated with adverse effects, particularly gastrointestinal disturbances, thus driving the search for safer alternatives from natural sources. Centella asiatica (pegagan) is a medicinal plant traditionally used for various ailments, containing bioactive compounds with potential analgesic properties. Objective: This study aimed to evaluate the analgesic activity of ethanol extract of Centella asiatica leaves in male white mice (Mus musculus) and to determine the most effective dose. Methods: A true experimental study with pretest-posttest control group design was conducted involving 25 male mice randomly assigned into five groups (n=5 each): positive control (paracetamol 65 mg/kgBW), negative control (1% Na-CMC), and three treatment groups receiving ethanol extract at doses of 100, 150, and 200 mg/kgBW. The extract was prepared by maceration using 70% ethanol and subjected to phytochemical screening. Analgesic activity was evaluated using the tail flick method, with latency time measured at 30, 60, 90, and 120 minutes post-administration. Data were analyzed using Wilcoxon signed-rank test and Mann-Whitney U test at 95% confidence level. Results: Phytochemical analysis revealed the presence of alkaloids, flavonoids, saponins, and tannins in the extract, while steroids were not detected. The 100 mg/kgBW dose demonstrated the most consistent and significant analgesic activity, with statistically significant differences (p < 0.05) observed at 60, 90, and 120 minutes compared to pre-test values. This dose achieved the highest percentage of analgesia (63.09%) at 120 minutes, which was significantly superior to the positive control group. The 150 mg/kgBW dose showed inconsistent effects, while the 200 mg/kgBW dose exhibited comparable activity but with less consistency. Conclusion: The ethanol extract of Centella asiatica leaves possesses significant analgesic activity in mice, with the optimal dose of 100 mg/kgBW. The analgesic effect is likely mediated through the inhibition of cyclooxygenase enzymes and subsequent reduction of prostaglandin synthesis, supported by the presence of flavonoids, alkaloids, and triterpenoid compounds. These findings support the potential development of Centella asiatica as a standardized herbal analgesic agent.